The meaning of alumni / Crystal Charlene Charles - Charles, Crystal Charlene (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The definition of an alumni are; people who had attended or graduated from a certain university, college or school in the past. People who have associated with the same organization in the past. One can be an alumni even without graduating. An ex employee of an organization or contributor are example of the term. The masculine plural alumni is alumnus which refers to both men and women, or solely men. The term alumni is derived from the Latin word for student. Because this word's Latin base is masculine, it has historically been used to refer to men.